Students’ Mathematical Critical Thinking Ability Reviewed from Learning Motivation in Problem Based Learning Model Assisted by Google Sites - Safaatullah, Muh. Fajar; Pangestu, Abdil Munir; Amidi, Amidi (Unnes Journal of Mathematics Education, 2025)
This study aims to analyze students' critical thinking skills through the Google Sites Problem Based Learning (PBL) model, both from the aspect of classical completeness and its superiority compared to conventional models, as well as the effect of learning motivation on critical thinking skills. Research also describes students' critical thinking skills based on the level of learning motivation. The method used is a mixture with sequential explanatory design, where the quantitative approach uses the post-test only control group design. The research population is all students of class VIII of SMP Negeri 26 Semarang, with samples of class VIII A as an experimental and VIII B group as a control group. Research instruments in the form of a test of mathematical critical thinking skills, learning motivation questionnaires, and interviews, with data analysis using IBM SPSS 22. The results show that the PBL model assisted by Google Sites reaches classical completeness and is more effective than conventional models. Learning motivation has an influence of 38.5% on critical thinking skills. Further analysis shows that students with high motivation meet all indicators of critical thinking abilities, students with motivation are superior to indicators of interpretation, analysis, and evaluation, while students with low motivation are only superior to indicators of interpretation and analysis. This finding confirms that the PBL model assisted by Google Sites is effective in improving the ability of students' mathematical critical thinking, with learning motivation as one of the main supporting factors.